Perturbation of Urbanization to Earth's Surface Energy Balance. Issue 8 (26th April 2021) - Shen, Pengke; Zhao, Shuqing; Ma, Yongjing
Abstract: Urbanization, one of the most dramatic forms of land conversion, modifies local climatic environments and threatens human life and health. Here we use the space‐for‐time approach combined with satellite data to quantify the potential perturbation of surface energy balance and land surface temperature (LST) caused by urbanization at global scale. We estimate that collectively +2.4°C, +0.9°C, and +1.7°C potential changes for annual daytime, nighttime, and mean LST could be triggered when land surface converted from natural area to urban use, due primarily to the decline of latent heat during months from April to October (−23.9–−3.2 W m −2 ), and the reduced sensible heat and ground heat storage in other months (−5.2–−2.4 W m −2 ). Urbanization perturbation to surface energy balance and temperature exhibit conspicuous spatial heterogeneity (i.e., varying with latitude and climate zones) and temporal asymmetries (i.e., diurnal and seasonal: strong in summer daytime and weak in winter nighttime). These spatial‐temporal variations are interrelated closely with local background climate‐vegetation regimes, as indicated by strong correlations between urbanization perturbation to surface biophysical effects and precipitation, temperature, vegetation index across regions and months. Our findings provide empirical evidence that biophysical mechanisms of urbanization need to be considered in predicting future trajectories of climate change and local susceptibility of surface energy balance should be accounted for when evaluating urbanization effects and mitigating urban heat. Key Points: Space‐for‐time approach is used to quantify surface energy perturbation and temperature (LST) change caused by global urbanization Surface warmings (e.g., +1.7°C for annual mean LST) could be triggered due primarily to decline in latent heat during April to October Surface energy perturbation exhibits spatial heterogeneity and temporal asymmetries, interrelating with local climate‐vegetation regimes